Mapping Research Trends on Archives : A Bibliometric Study (Universitas Terbuka, 2024)
The development of archival research in Indonesia can be determined by carrying out bibliometric analysis. This research was conducted to provide a reference to researchers in the archival field regarding current trends in archival research. This research aims to explore the development of research in the field of archives from 2019 to 2024. Data obtained and processed from Google Scholar using Harzing's Publish and Perish (PoP) software amounted to 930 articles. Data analysis using VOSviewer visualization. The research results show that the most researched research theme is